Paradise of cities : Venice in the 19th century - Norwich, John Julius, 1929-2018 (New York : Doubleday, 2003)
"John Julius Norwich, the author of A History of Venice, traces the transformation of Venice from a proud independent state into a dazzling dreamscape that attracted artists, writers, and composers from around the world. In a strikingly effective departure from straight narrative history, he tells the story of Venice through the experiences and reactions of such famous nineteenth-century visitors as Napoleon Bonaparte, Lord Byron, John Ruskin, Henry James, Richard Wagner, James Whistler, and Robert Browning." "Paradise of Cities is at once a history and a travel guide. Filled with vintage photographs and full-color reproductions of period paintings, it conveys both the misfortune of Venice's decline and the magnificence of its eternal beauty."--Jacket
Includes bibliographical references (p. 319-323) and index.
Keywords: Intellectuals -- Italy -- Venice -- Biography; Venice (Italy) -- Civilization -- 19th century; Venice (Italy) -- Intellectual life -- 19th century